Proceedings of the 2016 ACM Conference on International Computing Education Research 2016
DOI: 10.1145/2960310.2960332
|View full text |Cite
|
Sign up to set email alerts
|

"I Don't Code All Day"

Abstract: Stereotypes of computer scientists are relevant to students' performance and feelings of belonging. While e↵orts exist to change these stereotypes, we argue that it may be possible to challenge a student's belief that stereotypes of computer scientists are relevant to whether they can become a computer scientist. In our previous work, we presented a model of five factors that influence students' decisions to major in computer science (CS). Data were collected from interviews with 31 students enrolled in introd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…As women, Anne and LStew struggled with the CS stereotype, and a sense of not belonging, especially prior to their senior year. This phenomenon aligns with various reports on women in computer science (Falkner, Szabo, Michell, Szorenyi, & Thyer, 2015;Graham & Latulipe, 2003;Irani, 2004;Lewis, Anderson, & Yasuhara, 2016;Outlay, Platt, & Conroy, 2017;Wang, Hejazi Moghadam, & Tiffany-Morales, 2017). Lewis, Anderson, and Yasuhara (2016) describes this stereotype as "singularly focused on CS, asocial, competitive, and male" (p.30).…”
Section: The Participantssupporting
confidence: 87%
“…As women, Anne and LStew struggled with the CS stereotype, and a sense of not belonging, especially prior to their senior year. This phenomenon aligns with various reports on women in computer science (Falkner, Szabo, Michell, Szorenyi, & Thyer, 2015;Graham & Latulipe, 2003;Irani, 2004;Lewis, Anderson, & Yasuhara, 2016;Outlay, Platt, & Conroy, 2017;Wang, Hejazi Moghadam, & Tiffany-Morales, 2017). Lewis, Anderson, and Yasuhara (2016) describes this stereotype as "singularly focused on CS, asocial, competitive, and male" (p.30).…”
Section: The Participantssupporting
confidence: 87%
“…is could partially explain how coding bootcamps have achieved near gender parity [19] and may provide insights on how other computing programs can increase diverse engagement. Stereotypes of "nerdiness" and "intelligence" also formed informal boundaries for bootcamp students, as found elsewhere [2,5,10]. e class divide, largely a ributed to previous experience, also matched other contexts [12,13,21].…”
Section: Discussionmentioning
confidence: 60%
“…Stuck in the Shallow End: Education, Race and Computing by Margolis, Estrella, et al [12] examined the racial gap in high school CS, nding barriers that included lack of access to classes (formal boundary), cultural expectations on who the classes were for, feelings of isolation in classes, divisions within classes between those who "have it or don't have it" (informal boundaries), and lack of social support (personal obstacle). Additional studies found participation and success in computing programs depended on background experience [2,27], comfort level [27], sense of belonging and stereotypes (disproportionately negatively a ecting women) [2,5,10,16], view of self as an "insider" [21], and believed role of luck [27].…”
Section: Barriers In Computing Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, stereotypes lead to consider computer scientists as singularly focused, asocial, competitive, male gures [9].…”
Section: Context and Motivationmentioning
confidence: 99%